2000
DOI: 10.1016/s0895-7061(99)00118-1
|View full text |Cite
|
Sign up to set email alerts
|

Human G-protein  3 subunit variant is associated with serum potassium and total cholesterol levels but not with blood pressure

Abstract: The activity of a sodium-proton exchanger is enhanced in the patients with essential hypertension and regulated via G-protein, which is a signal transducer between receptors and intracellular effectors. A recent study has revealed that a novel variant (C825T) in exon 10 of the gene encoding the beta3 subunit of heterotrimetric G proteins (GNB3) is a genetic factor predisposing to hypertension in Caucasians. We examined the association between GNB3/ C825T and blood pressure, lipids, electrolytes, and other para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 19 publications
8
51
2
Order By: Relevance
“…Several investigators have issued several nongenetic factors as predictors of hypertension status, like obesity, smoking habits, nutritional habits, physical activity and psychological status. [1][2][3][4][5][6][7] The results from our analysis remained similar, after controlling for several of the aforementioned factors, which enhance the eligibility of our reports.…”
Section: Demonstrated That Insupporting
confidence: 70%
See 1 more Smart Citation
“…Several investigators have issued several nongenetic factors as predictors of hypertension status, like obesity, smoking habits, nutritional habits, physical activity and psychological status. [1][2][3][4][5][6][7] The results from our analysis remained similar, after controlling for several of the aforementioned factors, which enhance the eligibility of our reports.…”
Section: Demonstrated That Insupporting
confidence: 70%
“…However, there are other studies that have failed to show significant results regarding the relationship between the polymorphism C825T in the GNB3 gene and blood pressure levels. [5][6][7] Therefore, we sought to evaluate the relationship between the C825T polymorphism in the GNB3 gene with the levels of blood pressure, and the prevalence of hypertension, in a Greek population-based sample of adults.…”
mentioning
confidence: 99%
“…47 These discordant findings suggest that ethnic or genetic background, 8 lifestyle or various environmental factors may modulate the potential effect of the C825T allele on blood pressure. The frequency of the T allele was 0.32 in our Caucasian populations, but it is approximately 0.50 in Japanese 45,46 or native Americans 48,49 and 0.75 42,46 in black populations. One possible mechanism for the higher systolic blood pressure might be chronic sodium retention and expansion of the circulating volume as a consequence of the higher activity of the Na + /H + exchanger.…”
Section: Discussionmentioning
confidence: 55%
“…36 Published studies on the possible influence of the GNB3 C825T polymorphism reported inconsistent results. The 825T allele was associated with increased blood pressure [40][41][42] or increased risk of hypertension 22,43,44 in Germans, 22,39,42,44 Australian White hypertensive patients 41 and Caribbean or West African Blacks, 43 but not in French, 22 Irish, 22 Japanese 45,46 or African Americans. 47 These discordant findings suggest that ethnic or genetic background, 8 lifestyle or various environmental factors may modulate the potential effect of the C825T allele on blood pressure.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation